Mobile Learning Model for Children with Special Learning Needs - Tan, Ping Ping; Presella Sherrilyn, Dennis; Azlina Ahmadi, Julaihi; Goh, Maybelline Boon Ling (2021)
The mobile learning developed for children with special learning needs have limited users even within the same learning disability because severity in learning disability varies greatly even within a specific learning disability. Mobile learning developed for these children currently uses the same model used by any mobile application development where it caters for the masses rather than focusing on personalisation. The objective of this paper is to propose a mobile learning model for children with special learning needs, named APIE. ADDIE model is a generic instructional system design model that consists of processes: Analysis, Design, Develop, Implement and Evaluate. APIE is a modification from the ADDIE model, which makes APIE a mobile learning application development model. APIE iterates the design and develop processes under the Personalisation stage to explore the most suitable way for customisation for individual learning. APIE is applied to the development of a mobile learning for Dyslexic Children to assist the children to read and spell. Through APIE, a mobile learning application, DysleRead is produced. DysleRead integrates two classroom approaches: sight word and phonic where teachers can set and monitor individual learning needs of the children. The teachers find DysleRead helpful to teach the children. This shows that the mobile learning application produced using APIE meets the objective to cater for personalisation within a specific learning needs without undermining the role of the teachers. Hypothetically, APIE model is applicable to other special learning needs too.